Efficient robust optimization based on polynomial chaos and tabu search algorithm - Wu, Lie; Yang, Shiyou; Bai, Yanan; Machado, Jose Marcio [UNESP] (IOS Press, 2012)
The study of robust design methodologies and techniques has become a new topical area in design optimizations in nearly all engineering and applied science disciplines in the last 10 years due to inevitable and unavoidable imprecision or uncertainty which is existed in real word design problems. To develop a fast optimizer for robust designs, a methodology based on polynomial chaos and tabu search algorithm is proposed. In the methodology, the polynomial chaos is employed as a stochastic response surface model of the objective function to efficiently evaluate the robust performance parameter while a mechanism to assign expected fitness only to promising solutions is introduced in tabu search algorithm to minimize the requirement for determining robust metrics of intermediate solutions. The proposed methodology is applied to the robust design of a practical inverse problem with satisfactory results.
Keywords: Robust design; polynomial chaos; design optimization; tabu search algorithm